Enterococcus faecalis Isolated From Infant Feces Inhibits Toxigenic Clostridioides (Clostridium) difficile - Romyasamit, Chonticha (Front Pediatr, 2020)
Clostridioides (Clostridium) difficile infection is implicated as a major cause of antibiotic-associated diarrhea in hospitals worldwide. Probiotics, especially lactic acid bacteria, are the most frequently used alternative treatment. This study aims to identify potential probiotic enterococci strains that act against C. difficile strains and exert a protective effect on colon adenocarcinoma cells (HT-29 cells). To this end, nine Enterococcus strains isolated from the feces of breast-fed infants were investigated. They were identified as E. faecalis by 16s rRNA sequencing and MALDI-TOF. The probiotic properties including their viabilities in simulated gastrointestinal condition, cell adhesion ability, and their safety were evaluated. All strains exhibited more tolerance toward both pepsin and bile salts and adhered more tightly to HT-29 cells compared with the reference probiotic strain Lactobacillus plantarum ATCC 14917. Polymerase chain reaction (PCR) results exhibited that six of nine strains carried at least one virulence determinant gene; however, none exhibited virulence phenotypes or carried transferable antibiotic resistance genes. These strains did not infect Galleria mellonella when compared to pathogenic E. faecalis strain (p < 0.05). Moreover, their antibacterial activities against C. difficile were examined using agar well-diffusion, spore production, and germination tests. The six safe strains inhibited spore germination (100 – 98.20% ± 2.17%) and sporulation, particularly in C. difficile ATCC 630 treated with E. faecalis PK 1302. Furthermore, immunofluorescence assay showed that the cytopathic effects of C. difficile of HT-29 cells were reduced by the treatment with the cell-free supernatant of E. faecalis strains. These strains prevented rounding of HT-29 cells and preserved the F-actin microstructure and tight junctions between adjacent cells, which indicated their ability to reduce the clostridial cytopathic effects. Thus, the study identified six E. faecalis isolates that have anti-C. difficile activity. These could be promising probiotics with potential applications in the prevention of C. difficile colonization and treatment of C. difficile infection.